Guyana : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2018)
Economic growth slowed down, but became more broad-based. In 2017, real GDP growth was 2.1 percent, with the non-mining GDP rebounding from its contraction in 2016. The external balance turned negative due to weaker than expected export growth and higher oil prices. Inflation remains relatively low, and the monetary stance accommodative. Oil production is expected to commence in 2020, and additional oil discoveries have significantly improved the medium- and long-term outlook.